2015
DOI: 10.1210/en.2015-1154
|View full text |Cite
|
Sign up to set email alerts
|

Deleting the Redundant TSH Receptor C-Peptide Region Permits Generation of the Conformationally Intact Extracellular Domain by Insect Cells

Abstract: The TSH receptor (TSHR) extracellular domain (ECD) comprises a N-terminal leucine-rich repeat domain and an hinge region (HR), the latter contributing to ligand binding and critical for receptor activation. The crystal structure of the leucine-rich repeat domain component has been solved, but previous attempts to generate conformationally intact complete ECD or the isolated HR component for structural analysis have failed. The TSHR HR contains a C-peptide segment that is removed during spontaneous TSHR intramo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
(38 reference statements)
1
2
0
Order By: Relevance
“…To simplify purification of intact receptors for structural studies, we generated a TSHR construct devoid of the C-peptide, which could be purified as a single intact receptor construct. In agreement with prior studies demonstrating that this region is not required for proper receptor folding and signaling 14 , removal of the Cpeptide did not affect TSH or TSI activation of Gs signaling (Supplementary Fig. 1).…”
Section: Structure Of Tsh-activated Tshr Bound To Gssupporting
confidence: 92%
See 1 more Smart Citation
“…To simplify purification of intact receptors for structural studies, we generated a TSHR construct devoid of the C-peptide, which could be purified as a single intact receptor construct. In agreement with prior studies demonstrating that this region is not required for proper receptor folding and signaling 14 , removal of the Cpeptide did not affect TSH or TSI activation of Gs signaling (Supplementary Fig. 1).…”
Section: Structure Of Tsh-activated Tshr Bound To Gssupporting
confidence: 92%
“…TSHR is naturally proteolytically cleaved within the extracellular domain leading to removal of residues 317 to 366, a region termed the "C-peptide" 13 . While the physiological relevance of Cpeptide excision remains unclear, previous biochemical studies have demonstrated that cleavage in this domain leads to receptor instability 14 . To simplify purification of intact receptors for structural studies, we generated a TSHR construct devoid of the C-peptide, which could be purified as a single intact receptor construct.…”
Section: Structure Of Tsh-activated Tshr Bound To Gsmentioning
confidence: 99%
“…TSHR used in our studies contains a deletion of residues 317-366 in the hinge region, which is naturally removed from matured TSHR 15 . It has been shown that the region of residues 317-366 is not required for TSHR folding and signaling, and its deletion increases TSHR stability 15,16 . In addition, a TSHR constitutively active mutation, S281I, was also introduced to enhance the assembly of the TSH-TSHR-Gs complex 6,17 .…”
Section: Structure Of the Tsh-tshr-gs Complexmentioning
confidence: 99%